Política de indexação para construção de catálogos coletivos em bibliotecas universitárias - Rubi, Milena Polsinelli [UNESP] (2008)
The indexing policy must be represented by means of a philosophy that reflects the system's aims. One of the aspects concerning the indexing policy is relating to the data retrospective conversion and the compatibility of indexing language among members of a same cooperative system. The appearing of the technologies made it possible to think of cooperation among libraries and, consequentely, of cooperative cataloguing. The new scene of the cataloguing brought a great advance to the field: agility of cataloguing, decreasing the time of service and optimizing this process, since it is possible the utilization of bibliographic records copied from other databases. Nevertheless, there were other consequence: the process of subject's cataloguing (indexing) was simplified reducing it to a simple operation of copy, taking into account the document's form, disregarding the content. This practice simplification refers to a theoretical and high discussed conceptual matter, not yet well sedimented in Librarianship: the concept of indexing and subject cataloguing. The thesis of this research considers that the incoherences made during the indexing are results of non-discerment between descriptive cataloguing and subject cataloguing by the librarian, of the absence of policy and handbook of indexing for libraries which would be useful as guidelines to the indexer's work and instrument to his education in service, besides a systematics to identify concepts. We intend to present a theoretical methodological proposal for the working up of guidelines of indexing policy for the building of cooperative catalogs in university libraries, by means of the indexing process, from the socio-cognitive approach with librarians and users in the context of the university library, and in the conceptual perspective of the theoretical aspects that involve the indexing and the subject cataloguing.